Serum IP-10 Levels Correlate with the Severity of Liver Histopathology in Patients Infected with Genotype-1 HCV - You, Chan Ran (The Korean Society of Gastroenterology; the Korean Society of Gastrointestinal Endoscopy; the Korean Association for the Study of the Liver; the Korean Society of Neurogastroenterology and Motility; Korean Association for the Study of Intestinal Diseases; Korean College of Helicobacter and Upper Gastrointestinal Research; Korean Society of Pancreatobiliary Diseases, 2011)
BACKGROUND/AIMS: Interferon-γ-inducible protein 10 (IP-10) plays important roles in the pathogenesis of hepatitis C virus (HCV) infection. We investigated the association between serum IP-10 levels and liver pathology in patients with chronic HCV infection. METHODS: The serum IP-10 concentration was assessed in 85 patients with chronic HCV infection using a solid phase sandwich enzyme-linked immunosorbent assay, and a liver biopsy specimen was obtained. The pathology was scored using the Knodell histologic activity index (HAI). RESULTS: Of the 85 patients, 58 had genotype 1 HCV infection, 21 had genotype non-1, and 6 were undetermined. The serum IP-10 levels did not differ between patients infected with genotype 1 and genotype non-1 (p=0.472). In patients with genotype 1 infection, the total HAI score and the stage of fibrosis were highly correlated with the serum IP-10 level (r=0.555, r=0.578, p<0.001). Furthermore, the serum IP-10 concentrations of patients with severe fibrosis (stages 3, 4) were higher than those of patients with mild fibrosis (stages 0 to 2; 214.4 vs. 72.3 pg/mL, p=0.002) among patients with genotype 1 infection. However, in patients without genotype 1 infection, the histopathology was not associated with the serum IP-10 level. A multivariate analysis showed that serum IP-10 was an independent predictor of fibrosis (stages 3, 4) in patients with genotype 1 infection (odds ratio, 1.034; 95% confidence interval, 1.006 to 1.064; p=0.018). CONCLUSIONS: Serum IP-10 concentration was significantly correlated with the severity of liver histology in genotype 1 HCV infection.